FAKTOR YANG MEMPENGARUHI NIAT KEAKTIFAN LANSIA DALAM MENGIKUTI SENAM LANSIA DI INSTALASI GERIATRI RSUP Dr. KARIADI SEMARANG - Dwi Lestari Tantinis; Bagoes Widjanarko; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Tendency of increase in the elderly population need to be considered to be healthy. One of maintaining eledery heatlh with preventive effort, namely gymnastics for eledery. Gymnastics for elderly can slow the loss of function caused by cardiovascular disease. This study intend to determine factors that affect the interests of the elderly in participating in gymnastics elderly in Installation Geriatri RSUP Dr. Kariadi Semarang. This type of research is descriptive analysis method quantitative techniques cross-sectional study. The population of this research is elderly who attends on gymnastics. Total sample of 53 elderly respondents with total sampling technique. Analyzed using univariate and bivariate. Results of univariate analysis showed the majority of participants classified as gymnastics elderly aged or elderly aged 60-74 years by 86,8%, most participants gymnastics elderly female 69,8%, elderly gymnastics majority of participants have completed formal education up to the tertiary level at 79,2%. The bivariate analysis using Chi Square test (α = 0,05). The results of the bivariate analysis showed variable related is attitudinal variables (ρ value 0,002). Variable subjective norm (ρ value 0,029). While unrelated variable is the variable age (ρ value 1,957), variable gender (ρ value 1,000) and education variables (ρ value 0,455).